Survival and Success of Dental Implants in Patients with Autoimmune Diseases: a Systematic Review - Emil Hyldahl; Klaus Gotfredsen; Anne Marie Lynge Pedersen; Simon Storgård Jensen (eJournal of Oral Maxillofacial Research)
Objectives: The purpose of this systematic review is to disclose the impact of autoimmune diseases and their medical treatment on dental implant survival and success.